Semantics Analysis of Sentences, Utterances, and Presuppositions in The Story Five Feet Apart by Rachael Lippincott - Emir Fahim Ramzy; Fajar Shakti Wiraatmaja; Keyza Alifah Mokginta; Rahmawati Jaymitha; Hilma Safitri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Rachael Lippincott's 2019 short tale "Five Feet Apart" is examined in this study with an emphasis on the language, words, and premises used. His expressions are a tangible depiction of the phrases they contain, and the sentences themselves have a sound and comprehensive grammatical structure. The word "presupposition" refers to assumptions that are implicit in meaning. Understanding language structure, application in practical settings, and inferred meanings during communication encounters are the goals of this study. Semantics is analyzed using descriptive qualitative research methods. Based on the research results, determining semantic meaning requires an understanding of the differences between sentences and expressions, although presuppositions can reflect linguistic opinions or communication strategies. George Yule (1996) and Charles W. Kreidler (1998) are referenced for the discussed hypotheses.